A fully coupled meso-scale electro-chemo-mechanical phase field method for corrosion-induced fracture in concrete. (1st April 2023) - Zhang, Peng; Dai, Jian-Guo; Sekhar Das, Chandra; Zheng, Jian-Jun
Highlights: A fully coupled meso -scale electro-chemo-mechanical phase field model is proposed to simulate the corrosion mechanism in concrete structures; The mass transport process of moisture, chloride ions and oxygen are well captured by the model; The corrosion-induced damages in both mortar and interfacial transition zones are vividly simulated. The model is validated by existing test data and used to reveal the effects of various structural and environmental parameters. Abstract: Corrosion-induced concrete cover deterioration is a major factor affecting the serviceability of the reinforced concrete (RC) structures. The entire corrosion process, including mass transport, physical/chemical/electrochemical reactions, and cover cracking, occurs at the meso -scale. This paper developed a fully coupled meso -scale electro-chemo-mechanical phase field method to accurately simulate the corrosion mechanism in RC structures. The simulation begins with the mass transport process in the concrete, including the moisture, chloride ions and oxygen. When the chloride concentration at the rebar surface reaches a critical value, corrosion initiates and then propagates. A meso -scale phase field model is adopted for characterizing the corrosion-induced damage in both mortar and interfacial transition zones (ITZs). In addition, crack direction dependent diffusivity tensors are proposed to consider the influence of damage on the mass transport process. The proposed numerical method is verified by previously reported experimental results, showing its ability to conduct high-fidelity simulations of corrosion-induced fracture in RC structures. Parametric studies are carried out to investigate the effect of aggregate distribution, cover thickness, relative humidity, and temperature on the corrosion process.